The theory of corporate finance - Tirole, Jean (Princeton University Press, 2006)
This text conveys the organizing principles that structure the analysis of key management and public policy issues, such as the reform of corporate governance and auditing; the role of private equity, financial markets, and takeovers; and the design of managerial incentive packages.